Tyrosine kinase Eph receptor A6 sensitizes glioma‐initiating cells towards bone morphogenetic protein‐induced apoptosis. Issue 11 (20th September 2019) - Raja, Erna; Morikawa, Masato; Nishida, Jun; Tanabe, Ryo; Takahashi, Kei; Seeherman, Howard J.; Saito, Nobuhito; Todo, Tomoki; Miyazono, Kohei
Abstract: Bone morphogenetic protein (BMP) signaling plays important roles in glioblastoma multiforme (GBM), a lethal form of brain tumor. BMP reduces GBM tumorigenicity through its differentiation‐ and apoptosis‐inducing effects on glioma‐initiating cells (GIC). However, some GIC do not respond to the tumor suppressive effects of BMP. Using a phosphoreceptor tyrosine kinase array, we found that EPHA6 (erythropoietin‐producing hepatocellular carcinoma receptor A6) phosphorylation was regulated by BMP‐2 signaling in some GIC. Analysis of The Cancer Genome Atlas showed that EPHA6 expression was lower in patients with GBM than in the normal brain, and that high EPHA6 expression was correlated with better prognosis. EPHA6 receptor increased the susceptibility of both sensitive and resistant GIC to BMP‐2‐induced apoptosis. The cooperative effect on apoptosis induction depended on the kinase activity of BMP type I receptor but was independent of EPHA6 kinase function. Overexpression of the EPHA6 receptor in GIC resulted in the formation of a protein complex of EPHA6 receptor and the BMP type I receptor ALK‐2, which was associated with BMP‐induced apoptosis in GIC. Intracranial injection of GIC into nude mice showed that gain‐of‐function of EPHA6 together with BMP‐2 pretreatment slowed GBM tumor progression in the mouse brain and promoted mouse survival. In summary, EPHA6 together with BMP‐2 signaling led to apoptotic cell death in GIC, and thus is a putative tumor suppressor in GBM. Abstract : GIC infected with ad‐LacZ, ad‐EPHA6‐WT (wild‐type), or ad‐EPHA6‐KD (kinase‐dead) with or without BMP type I receptor kinase inhibitor LDN193189 and BMP‐2. Inhibition of BMP type I receptor kinase blocked apoptosis induced by the cooperation of EPHA6 and BMP‐2.